2012
DOI: 10.1590/s1415-790x2012000200013
|View full text |Cite
|
Sign up to set email alerts
|

Confiabilidade interobservador da classificação internacional de atenção primária em uma unidade de atenção básica à saúde

Abstract: ResumoAvaliou-se a confiabilidade interobservador da Classificação Internacional de Atenção Primária na codificação de queixas relatadas em unidade básica de saúde pública, por meio de uma amostra de 300 atendimentos. Os motivos de consulta foram registrados por médicos do serviço, e sua codificação realizada por duas pesquisadoras. A concordância entre as classificadoras em relação ao número de motivos codificados foi calculada por meio do kappa ponderado; para as demais análises (capítulos e códigos completo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(3 reference statements)
0
2
1
1
Order By: Relevance
“…There are, however, at least two studies comparing encoders with different levels of experience or information. 5,7 Again, the validity of the encoding in this study was higher than or as high as that found in those studies, partly because the students in this study were encoding previously abstracted data.…”
Section: Comparison With the Scientific Literaturecontrasting
confidence: 62%
See 1 more Smart Citation
“…There are, however, at least two studies comparing encoders with different levels of experience or information. 5,7 Again, the validity of the encoding in this study was higher than or as high as that found in those studies, partly because the students in this study were encoding previously abstracted data.…”
Section: Comparison With the Scientific Literaturecontrasting
confidence: 62%
“…While localization takes precedence over etiology in the chapters, the diagnosis component has etiological sub-components: infection, neoplasm, injury, congenital and other diagnoses. 2,3 Although the reproducibility of ICPC encoding by medical doctors has been studied, [3][4][5][6][7][8] less is known about the reliability of the encoding by medical students. Medical students might need to use the ICPC Objetivo: Estimar la confiabilidad y la validez de la codificación de motivos de consulta y problemas de salud por estudiantes utilizando la Clasificación Internacional de Atención Primaria, 2ª edición (CIAP-2).…”
Section: Introductionmentioning
confidence: 99%
“…Different encodings for the same episode of care in primary care does not imply inadequacy of the coding system and does not affect the recognition of the morbidity profile of a population group 8 . A recent national study reported good interobserver reliability using the ICPC-2, which indicates a good performance of the classification code for reasons of care in primary care, even from logs in medical records 21 . Other aspects of the classification tend to be better studied from computerized analyses, which is still not a reality in the country.…”
Section: Discussionmentioning
confidence: 96%
“…Essa população é registrada no Sistema Único de Saúde (SUS) e conhecida de acordo com os fatores de risco e condições de saúde para que se estabeleçam as RAS a partir da APS. 8 Para isso, cabe a ressalva da distribuição dos pacientes em níveis de sequelas ocasionadas pós-covid 19, sendo de atenção maior voltada aos centros de especialização das UBS, que trabalhem com o apoio da fisioterapia e das técnicas especificas que desenvolvam a evolução de cada um, como princípios oferecidos pelo SUS. Pacientes internados em UTI apresentam perda de 20% da massa muscular da coxa na primeira semana de internação.…”
Section: Introductionunclassified